EVALUASI KINERJA PERSIMPANGAN BERSINYAL (STUDI KASUS JL. SIMPANG SULFAT UTARA – JL. SIMPANG SULFAT SELATAN – JL. TERUSAN SULFAT – JL. RAYA SULFAT) - Rifky Aldila Primasworo Rifky Aldila Primasworo; Blima Oktaviastuti Blima Oktaviastuti; Delan Efri Aldo Delan Efri Aldo (Jurnal Qua Teknika, 2022)
An intersection is a place that turns or branches from a straight line. Crossroads with signals, namely road users who pass through the intersection in accordance with the operation of the traffic signal. The sulphate signaled intersection has a high density level as a result of the heavy traffic volume and does not match the road capacity in Belimbing sub-district, Malang city. The research method is by field observation or data collection where the researcher records information through direct events that are being witnessed during the research, one of which is a traffic volume survey conducted using the average traffic survey (LHR) method. The average daily traffic survey is carried out for one week from Monday - Sunday, where the length of observation is 16 hours starting from 06:00 - 22:00 WIB. The evaluation results at the sulphate-signaled intersection show that the degree of saturation of the morning peak hours on each approach is 0.98 North, 1.38 South, 1.79 East and has exceeded the DS value required in the 1997 MKJI, namely 0.75. While the DS value in the Western approach is 0.71 and has met the DS value required in the 1997 MKJI. The predicted results of the sulfate signalized intersection in the 10th year show that the DS value in each approach is 1.10 North, 1.51 South, East 1.78 and West 1.08 and greatly exceeds the DS value in the 1997 MKJI which is 0.75. Changes in WINS, WLETS and making a direct left turn and redesigning cycle times are alternative solutions that are proven to increase the level of service at the intersection from F (obstructed current) to C (stable flow).